2020
DOI: 10.1038/s41377-020-00349-w
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the optical and electrical properties of MAPbBr3 single crystals via voltage regulation engineering and application in memristors

Abstract: Defect density is one of the most significant characteristics of perovskite single crystals (PSCs) that determines their optical and electrical properties, but few strategies are available to tune this property. Here, we demonstrate that voltage regulation is an efficient method to tune defect density, as well as the optical and electrical properties of PSCs. A three-step carrier transport model of MAPbBr3 PSCs is proposed to explore the defect regulation mechanism and carrier transport dynamics via an applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…Recently, for the popular investigated organic-inorganic halide perovskite materials CH 3 NH 3 PbI 3 (MAPbI 3 ), a direct optical study unraveled that the strong recombination at surface dominates the carrier lifetime losses and thus the performance criteria of the PSCs. [12,13] In addition, together with ion migration in the perovskite film, the interfacial recombination is recognized as a main factor for lots of the observed hysteresis behaviors, which increases the uncertainty of device performance. [14] Therefore, effective interfacial passivation strategies at the contacts interface to suppress the recombination becomes increasingly critical to achieving higher performance PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, for the popular investigated organic-inorganic halide perovskite materials CH 3 NH 3 PbI 3 (MAPbI 3 ), a direct optical study unraveled that the strong recombination at surface dominates the carrier lifetime losses and thus the performance criteria of the PSCs. [12,13] In addition, together with ion migration in the perovskite film, the interfacial recombination is recognized as a main factor for lots of the observed hysteresis behaviors, which increases the uncertainty of device performance. [14] Therefore, effective interfacial passivation strategies at the contacts interface to suppress the recombination becomes increasingly critical to achieving higher performance PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the diffusion of free carriers into the bulk region is induced, resulting in more fluorescence emission through the free carrier, thereby facilitating carrier transport and prolonging the free-carrier lifetime (τ 3 ). 63 It was found that the triple-cation perovskite films washed with 2I-Ac, 2Br-Ac, and 2Cl-Ac molecules exhibited a longer τ 3 than that of the control sample as shown in Figure 2 d. The significantly extended lifetime of the triple-cation perovskite films with these three molecules represents the successful suppression of defects by the severe carrier nonradiative recombination in the triple-cation perovskite bulk. As shown in Figure 2 d, the TRPL measurement shows that the τ 3 lifetime is increased from 30.29 to 110.60, 57.87, and 34.78 ns in washing with 2I-Ac, 2Br-Ac, and 2Cl-Ac molecules, respectively.…”
Section: Results and Discussionmentioning
confidence: 85%
“…Fast decay components correspond to an effective charge extraction from perovskite to the ETL layer, whereas s 2 and s 3 represent the radiative recombination of free carriers. 37,38 In addition, the LTP-SnO 2 sample exhibits a low PL decay time (s 1 ¼ 2.28, s 2 ¼ 7.24) compared to LT-SnO 2 (s 1 ¼ 2.48, s 2 ¼ 11.5), indicating an effective electron transfer from the perovskite to ETL. The average recombination lifetime (s avg ) is calculated using the equation below:…”
Section: Resultsmentioning
confidence: 99%
“…† The value of s 1 , s 2 , and s 3 correspond to the decay time of fast, intermediate, and slow component respectively. Fast decay components correspond to an effective charge extraction from perovskite to the ETL layer, whereas s 2 and s 3 represent the radiative recombination of free carriers 37,38. In addition, the LTP-SnO 2 sample exhibits a low PL decay time (s 1 ¼ 2.28, s 2 ¼ 7.24) compared to LT-SnO 2 (s 1 ¼ 2.48, s 2 ¼ 11.5), indicating an effective electron transfer from the perovskite to ETL.…”
mentioning
confidence: 99%